Pengaruh Tunjangan Kinerja Dan Lingkungan Kerja Terhadap Motivasi Kerja Pegawai Kantor Kementerian Agama Kota Medan - Sarmauli Silalahi; Martua Sitorus (Junal Ilmu Manajemen, 2018)
This study aims to find out how much influence the Performance Allowance and Work Environment on Work Motivation of Office Workers of the Ministry of Religion in Medan City and the dominant variable gives influence on Employee Work Motivation at the Office of Ministry of Religion in Medan. The population of respondents in this study were all employees in the Office of the Ministry of Religion in Medan totaling 85 employees. The number of samples is calculated using the Slovin formula, then a total sample of 70 employees is obtained. The results of this study indicate that the independent variables, namely the performance allowance and work environment have a positive and significant effect on the work motivation of Medan City Ministry of Religion office employees at 69.9%. The results of this study also showed that the dominant variable affecting work motivation of Medan City Ministry of Religion office employees was Performance Allowance.